Spatial models cannot compensate for sampling designs unstructured relative to isotopic variation: implications for baseline isoscape development in the Mediterranean Sea - Sarah Magozzi; Clive N. Trueman; Matthew R.D. Cobain; Kirsteen M. MacKenzie; Katie St. John Glew; José A. Canseco; Eric Díaz-Delgado; Emanuela Fanelli; Paola Rumolo; Joan E. Cartes; Boris Espinasse; Davide Agnetta; et al. (Progress in Oceanography, 2026)

Millennial Posidonia oceanica reefs reveal contrasting growth trajectories across temporal scales in the Central Mediterranean - Gabriele Rizzuto; Federica Paola Cassetti; Geraldina Signa; Giovanna Cilluffo; Cristina Andolina; Gianluca Quarta; Lucio Calcagnile; Salvatrice Vizzini; Agostino Tomasello (Marine Environmental Research, 2026)

Marine life under plastic threat: A systematic review of systematic reviews - Geraldina Signa; Giovanna Cilluffo; Namrata Srivastava; Cristina Andolina; Agostino Tomasello; Salvatrice Vizzini (Marine Pollution Bulletin, 2026)

Effects of alternative feeds on Paracentrotus lividus broodstock: Asseswesment of egg nutritional composition and larval development - Laura Ciriminna; Arnold Rakaj; Geraldina Signa; Alessandra Fianchini; Antonio Mazzola; Salvatrice Vizzini (Aquaculture, 2026)

Discovering a beach “cemetery” of a seagrass Posidonia oceanica barrier reef: Search for clues to reconstruct its origins - Agostino Tomasello; Geraldina Signa; Federica Paola Cassetti; Sante Francesco Rende; Giovanna Cilluffo; Vincenzo Pampalone; Salvatrice Vizzini (Estuarine, Coastal and Shelf Science, 2025)

Does transplanted Posidonia oceanica act as a sink or source of trace elements? Ecological implications for restoring polluted coastal areas - Geraldina Signa; Agostino Tomasello; Giovanna Cilluffo; Cecilia Doriana Tramati; Antonio Mazzola; Sebastiano Calvo; Salvatrice Vizzini (Journal of Environmental Management, 2024)

Aquaculture of emerging species in North-Eastern Atlantic and Mediterranean Sea: a systematic review on sea cucumber farming and potential development - Laura Ciriminna; Geraldina Signa; Giovanna Cilluffo; Arnold Rakaj; Salvatrice Vizzini (Frontiers in Marine Science, 2024)
Sea cucumbers are considered a traditional food delicacy in Asian countries. In last decades high market demand, uncontrolled exploitation and inadequate management have led to stock overexploitation, driving commercial interest in new target species and new areas. In recent years, Mediterranean and North-East Atlantic sea cucumbers have become fishing targets, and, due to overfishing, a significant decline of wild populations have been observed, with detrimental effects on benthic communities and ecosystems. Indeed, in addition to being an important economic resource, sea cucumbers play a key ecological role in benthic dynamics where they are involved as ecosystem engineers in the processing of organic matter in the detrital food web pathway. In this context, aquaculture can play a crucial role in supporting the conservation of natural stocks by reducing harvesting pressure on wild populations and enabling restoration programmes for depleted stocks. Commercial sea cucumber farming is already an established reality in the Indo-Pacific region, where it has become one of the most profitable sectors of aquaculture production. In Europe, on the other hand, sea cucumber aquaculture is still an emerging sector, whose development is hampered by poor and fragmented information on the farming requirements of native species. In this context, this systematic review was carried out with the aim of providing a comprehensive summary of the state of the art of farming practices of the European sea cucumbers considered as a target of commercial fisheries. A total of 34 original articles were included in this review, after title, abstract and full-text screening. The results highlighted a sharp increase in the number of studies over the last six years. Portugal, Turkey and Italy are the countries where most research has been carried out. Among the selected species, Holothuria tubulosa was the most studied, while only one article was found on Parastichopus regalis . The main aims of this review were i) to gather all available literature on the farming practices of North-East Atlantic and Mediterranean sea cucumber species, ii) to outline the most common farming practices, iii) to identify gaps and future directions in this emerging aquaculture sector.

3D-Reconstruction of a Giant Posidonia oceanica Beach Wrack (Banquette): Sizing Biomass, Carbon and Nutrient Stocks by Combining Field Data With High-Resolution UAV Photogrammetry - Agostino Tomasello; Alessandro Bosman; Geraldina Signa; Sante Francesco Rende; Cristina Andolina; Giovanna Cilluffo; Federica Paola Cassetti; Antonio Mazzola; Sebastiano Calvo; Giovanni Randazzo; Alfonso Scarpato; Salvatrice Vizzini (Frontiers in Marine Science, 2022)
Beach wracks are temporary accumulations of vegetal detritus that can be found along coastlines all over the world. Although beach wracks are often perceived as a nuisance for beach users, they play a crucial ecological role in carbon and nutrient connectivity across ecosystem boundaries, especially when they reach a relevant size, as in the case of the wedge-shaped seagrass accumulations called banquette . In this study, three-dimensional mapping of a giant Posidonia oceanica banquette was carried out for the first time using high-resolution UAV photogrammetry combined with field sampling and compositional and chemical analysis. The combined approach allowed a reliable estimation of the amount and spatial distribution of both vegetal biomass and sedimentary mass, as well as of total carbon, nitrogen and phosphorus content, revealing that i) banquette act as a sediment trap and represent hot spots of seagrass biomass and carbon accumulation; ii) banquette thickness, rather than the distance from the sea, influences the spatial distribution of all variables. Moreover, high-resolution digital elevation models (DEM) revealed discontinuous patterns in detritus accumulation resulting in an unknown banquette type here termed “Multiple Mega-Ridge banquette ” (MMR banquette ). On the one hand, this study highlighted the high potential of the UAV approach in very accurately 3D mapping and monitoring of these structures, with relevant implications for ecosystem service estimation and coastal zone management. On the other hand, it opened new questions about the role played by temporary beach wracks and, in particular, by P. oceanica banquette in the blue carbon exchange across land-ocean boundaries.

Environmental effects of tourism and its seasonality on Mediterranean islands: the contribution of the Interreg MED BLUEISLANDS project to build up an approach towards sustainable tourism - Cristina Andolina; Geraldina Signa; Agostino Tomasello; Antonio Mazzola; Salvatrice Vizzini (Environment, Development and Sustainability, 2021)
The Mediterranean basin is amongst the world’s main tourist destination, and its islands are a major attraction, being sites of historical, cultural and naturalistic importance. This is beneficial for the local economies, but it may also represent a great burden on the coastal environment, where other human pressures are concentrated. The awareness of detrimental side effects of tourism together with the importance to take into account social and economic facets has led to the concept of sustainable tourism, which, however, represents a goal far from being attained. A good opportunity to promote sustainable tourism was provided by the Interreg MED BLUEISLANDS project, whose main aim was to identify, address and mitigate the effects of the seasonal variation of waste generated by tourism on Mediterranean islands. Here, we present the methodological framework of the project aimed at biomonitoring coastal seawater in highly touristic sites using macroalgae as valuable bioindicators of seawater quality and improving its status through the implementation and assessment of mitigation measures that included also the involvement of stakeholders. Outcomes of the project highlighted the effectiveness of such an integrated approach, confirming the importance of choosing proper indicators and tools that can support the development of management plans aiming to mitigate environmental impact and foster sustainable tourism.